Equações elípticas singulares envolvendo o expoente crítico de Caffarelli-Kohn-Nirenberg e funções peso mudando de sinal - Guimarães, Mateus Balbino (Universidade Federal de São Carlos, 2012)
In this work we will study the existence of nonnegative nontrivial weak solutions to singular elliptic equations involving the critical Caffarelli-Kohn- Nirenberg exponent and sign-changing functions. For this purpose, we will make use of the variational method and its classical results as the Mountain Pass Theorem and the Ekeland’s Variational Principle. We also will use the well known Nehari manifold.
Keywords: Análise; Equações diferenciais elípticas; Existência de soluções; CIENCIAS EXATAS E DA TERRA::MATEMATICA